The Bro-Xre toxin-antitoxin modules in Weissella cibaria: inducing persister cells to escape tetracycline stress by disrupting metabolism - Xiang, Wen-Liang; Xiong, Jie; Wang, Han-Yang; Cai, Ting; Shi, Pei; Zhao, Qiu-Huan; Tang, Jie; Cai, Yi-Min (Frontiers in Microbiology, 2024)
Toxin-antitoxin (TA) modules are important mediators of persister cell formation in response to environmental stresses. However, the mechanisms through which persistence is controlled remain poorly understood. Weissella cibaria, a novel probiotic, can enter a persistent state upon exposure to tetracycline stress. This study found that the Bro-Xre TA modules of W. cibaria function as typical tetracycline regulators. The Bro-Xre TA modules were activated when exposed to tetracycline stress, and the released toxin Bro acted on various cellular metabolic processes, including energy, amino acid, and nucleotide metabolism. Among them, the genes related to intracellular energy pathways, such as PTS, EMP, HMP, TCA, and oxidative phosphorylation, were downregulated, leading to reduced ATP synthesis and proton motive force. This metabolic disruption resulted in cells adopting a persistent phenotype, characterized by an increase in cell length in W. cibaria. Additionally, the frequency of persister cells increased under tetracycline stress. These results provide a novel perspective for understanding the mechanism by which TA modules induce persistence in probiotics, allowing them to evade antibiotic stress through metabolic disruption.